ISIEM: A methodology to deploy a knowledge-based system to support bidding process. (November 2021) - Guillon, Delphine; Villeneuve, Eric; Merlo, Christophe; Vareilles, Elise; Aldanondo, Michel
Highlights: This article aims to assist companies in their bidding process. A bid model and a knowledge-based system are used to help formalize new bids. A methodology for deploying this knowledge-based system is proposed. The methodology is formally validated by a case study from a design company. Results are discussed based on tests carried out with four industrial companies. Abstract: When responding to calls for tenders, companies must elaborate on relevant bids relative to the needs and expectations of customers (for example, in terms of price and delay). We built and deployed a knowledge-based system (KBS) to aid companies when developing bids. Based on a pre-defined generic bid model, a methodology to support companies when deploying the KBS is proposed in this paper. To capture, formalize, and reuse knowledge relevant to bids, a combination of several approaches, such as taxonomy, constraint satisfaction problem, and case-based reasoning, is proposed. The methodology is composed of five steps: Initialization, Specialization, Implementation, Exploitation, and Maintenance . A case study from a company building electrical parts of harbor lifting devices illustrates our proposal and allows validating the proposed methodology.